A CROSS-SECTIONAL STUDY ON ADHERENCE TO LIFESTYLE MODIFICATION AMONG KNOWN HYPERTENSIVE PATIENTS IN UDUPI DISTRICT - SHETTY, PRASHANTH; N, KARTHIK RAO; RAU N, GURUKANTH; PATTANSHETTY, SANJAY M; KARANTH, DIVYA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Hypertension is the more prevalent non-communicable disease and is the major risk factors for the cardiovascular disease. Lifestyle modification plays a very important role in controlling or management of the hypertension. Hence, aim of this study is to assess the adherence and non-adherence to lifestyle modification among known hypertensive patients those who are visiting secondary care hospitals in Udupi District. Methods: This was a multi-centric hospital based cross-sectional study conducted at three secondary care hospitals. Samples were collected through convenient sampling. Standardized questionnaire used to collect data. Associations are obtained the help of frequencies, prevalence, and mean values, ANOVA test, Chi-square, and binary logistic regression were used for the analysis. Results: The mean age of the participants was 63.01±11.12 years. Males were 144 (42.2%) and females were 197 (57.8%) of the study population. It was found that the self-assessment is influenced by education level of participant (p=0.003) and time elapsed since diagnosis of hypertension (p<0.001). Majority of the participants from age group of 34 to 48 and 49 to 63 had good adherence to exercise, that is, 70.4% (19) and 74.6% (100), respectively, (p=0.001). Participants with awareness regarding risk factors and complications of hypertension showed good adherence to exercise. The patients, who adhered to exercise, also consumed less quantity of salt. Conclusion: Instilling positivity in mind of the patient regarding outcome of treatment and lifestyle modifications can help in controlling the high blood pressure and there by prevent cardiovascular and renal disease in the whole population.